On the curvature forms of nil space - Yüzbaşi, Zühal Küçükarslan; Bektaş, Mehmet; Yilmaz, Münevver Yildirim (My University, 2013)
In this work, we study structure equations in Nil space. Also, the submanifold of Nil space is given and sectional, Ricci curvatures in this submanifold are obtained by using Nil metric. © 2013 Academic Publications, Ltd.
Keywords: Nil space; Sectional and Ricci curvatures; Structure equations; Submanifold; Totally geodesic